Tingkat Kepercayaan Konsumen Terhadap Keputusan Pembelian Pada Marketplace Shopee di Kota Bandung - Adirama, Satria; Priadi, Muhammad Dadi; Yuniarsih, Yuyun (Melati Institute, 2024)
With the growth of e-commerce, consumer trust has become a critical aspect in online transactions. However, increasing cases of online fraud, such as products that do not match the description, raise concerns about consumer trust. This raises the question of how trust affects purchasing decisions in marketplaces such as Shopee.The purpose of the research is to evaluate how consumers' trust in Shopee affects their purchasing decisions. This is important to understand in the context of increasing cases of online fraud, which could damage the reputation of e-commerce platforms.Quantitative methodology was used with data collection through a survey. Data processing was done using SPSS version 27 to analyze the relationship between consumer trust and purchasing decisions.The results showed a strong significant relationship between consumer trust and purchasing decisions at Shopee. It was found that 77.3% of the purchase decision variable could be explained through consumer trust, indicating that trust is the most important factor in e-commerce.The conclusion of this study is that in the competitive world of e-commerce, consumer trust in platforms like Shopee is very important. This means that Shopee and similar platforms must continuously strive to build and maintain consumer trust to ensure long-term success.